Modern methods of determining the individual norm of volumes and premising intensity of the exercisable motor activity - Puhach, Y. (Slobozhanskyi herald of science and sport, 2020)
The problem of individual approach in the organization of physical activities always assumes need of accounting of the current functional state, the level of preparedness and according to it the choice of available physical activity on intensity and duration and also admissible complexity of its performance for the purpose of improving orientation of their use. All these criteria can be defined with success on condition of accounting of dynamics and individual norm of course by adaptation reaction to the offered physical activity. The tasks still remain insufficiently resolved in many ways that defined orientation of the stated results of the conducted researches.